Morphology modulation of artificial muscles by thermodynamic-twist coupling. Issue 1 (22nd September 2022) - Hu, Xiaoyu; Li, Jiatian; Li, Sitong; Zhang, Guanghao; Wang, Run; Liu, Zhongsheng; Chen, Mengmeng; He, Wenqian; Yu, Kaiqing; Zhai, Wenzhong; Zhao, Weiqiang; Khan, Abdul Qadeer; et al.
ABSTRACT: Human muscles can grow and change their length with body development; therefore, artificial muscles that modulate their morphology according to changing needs are needed. In this paper, we report a strategy to transform an artificial muscle into a new muscle with a different morphology by thermodynamic-twist coupling, and illustrate its structural evolution during actuation. The muscle length can be continuously modulated over a large temperature range, and actuation occurs by continuously changing the temperature. This strategy is applicable to different actuation modes, including tensile elongation, tensile contraction and torsional rotation. This is realized by twist insertion into a fibre to produce torsional stress. Fibre annealing causes partial thermodynamic relaxation of the spiral molecular chains, which serves as internal tethering and inhibits fibre twist release, thus producing a self-supporting artificial muscle that actuates under heating. At a sufficiently high temperature, further relaxation of the spiral molecular chains occurs, resulting in a new muscle with a different length. A structural study provides an understanding of the thermodynamic-twist coupling. This work provides a new design strategy for intelligent materials. Abstract : The artificial muscle with precise reversibility control by thermodynamic-twist coupling is applicable to different actuation modes, including elongation, contraction, and torsional rotation.